2018
DOI: 10.3389/fphys.2018.01037
|View full text |Cite
|
Sign up to set email alerts
|

Pain Control by Proprioceptive and Exteroceptive Stimulation at the Trigeminal Level

Abstract: The Gate Control Theory of pain, published more than half a century ago to explain nociceptive modulation of peripheral sensory input, assumes inhibition of incoming nociceptive (pain) information produced by mechanical stimulation. To verify the presence of such a gate control mechanism at the level of the human trigeminal system, we evaluated the effects on pain sensation of a proprioceptive trigeminal stimulation induced by mandibular extension. We found that such a stimulation, applied for 7 min, was effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…[27] Owing to complex neurological pathways, proprioception, and pain can interfere with each other through neurophysiological processing. [28] A previous study observed the effect of proprioception on pain control and found a significant increase in the antinociceptive effect induced by proprioceptive stimulation, [29] consistent with our study's findings, where the JPST group showed lower PPT values than the control group. Although pain management cannot directly result in improved motor performance in some respects, our study suggests that JPST could significantly improve shoulder motor function according to the DASH assessment by enhancing proprioception input of shoulder joints.…”
Section: Treatment For Central Sensitization and Chronic Painsupporting
confidence: 93%
“…[27] Owing to complex neurological pathways, proprioception, and pain can interfere with each other through neurophysiological processing. [28] A previous study observed the effect of proprioception on pain control and found a significant increase in the antinociceptive effect induced by proprioceptive stimulation, [29] consistent with our study's findings, where the JPST group showed lower PPT values than the control group. Although pain management cannot directly result in improved motor performance in some respects, our study suggests that JPST could significantly improve shoulder motor function according to the DASH assessment by enhancing proprioception input of shoulder joints.…”
Section: Treatment For Central Sensitization and Chronic Painsupporting
confidence: 93%
“…[35][36][37] Most experts in the field agree that pain is regulated by the gate control theory, which is also supported by a diverse range of evidence, including animal studies, clinical trials, as well as physiological and biochemical experiments. [38][39][40] The gate control theory of pain was first proposed by Melzack and Wall in 1965 and has been widely accepted by the scientific community. [41] According to Melzack and Wall's gate control theory of pain, pain signals are transmitted from the periphery to the spinal cord via fine fibers, mainly A-delta and C-fibers.…”
Section: Pain Controlmentioning
confidence: 99%
“…Thus, vibrotactile stimuli applied around the noxious stimulus-sensitive center reduce WDR neuronal responses to the nociceptive inputs through inhibition ( 24 ). In humans, touch mediated pain relief has been demonstrated for both the body parts innervated by dorsal root ganglia (DRG) neurons, as well as for orofacial regions innervated by trigeminal ganglion (TG) neurons ( 5 ). A quantitative study in humans, in which a painful laser stimulation was flanked by two touch stimuli at varying distances, showed that concurrent application of touch caused the subjects to rate the laser stimuli as less painful in a distance dependent manner, consistent with the receptive field properties of spinal WDR neurons ( 6 ).…”
Section: Introductionmentioning
confidence: 99%